The Influence of the Economic Students’ Motivations and Language Learning Strategies towards Their English Achievement in STIE Muhammadiyah Palopo - Muhammad Iksan; Dirham Dirham (Universitas Cokroaminoto Palopo, 2018)
The aims of this research were: (1) to investigate the students’ motivations, (2) to investigate the language learning strategies (LLSs) that are used by the students, (3) to investigate the level of students’ LLSs usage, and (4) to investigate the influence of the students’ motivations and the level of students’ LLSs usage towards their English competence. This research gave descriptions about the students’ motivations, LLSs that are used by the students, and the level of students’ LLSs usage. The sample of this research was 111 students that were taken from three classes of the first year students from three study programs, i.e. Ilmu Ekonomi, Manajemen, and Akuntansi. This research revealed that the students were categorized into high motivated to learn English where 70 students (63%) had high motivation, 25 students (23%) had very high motivation, 13 students (12%) had medium motivation, and 3 students (3%) had low motivation. This research also found that the students were dominantly used metacognitive strategies (44%), followed by compensation strategies (18%), affective strategies (14%), social strategies (10%), cognitive strategies (8%), and the least used strategies were memory strategies (6%). For the level of the students’ language learning strategies usage, the researcher found that the students level were categorized into medium, where 78 students (70%) mediumly used the LLSs, 30 students (27%) highly used the LLSs, 2 students (2%) lowly used the LLSs, and 1 student (1%) very highly used the LLSs.